Factors associated with outcomes of patients placed on tuberculosis treatment in the western geographic service area of Cape Town - Nyoni, Irene (Department of Public Health and Family Medicine, 2019)
Background In the Western Cape Province of South Africa, tuberculosis (TB) is a major health problem and in 2012 accounted for 7.40% of premature deaths. The Province has also experienced an increase in TB incidence in the past 20 years. Objectives The aims of the study were to describe the distribution of tuberculosis and identify risk factors associated with TB treatment outcomes in public sector tuberculosis facilities in the Western Geographic Service Area of the Cape Town Metropole District. Methods A cross sectional study was conducted using data collected in electronic TB registers from June 2011 to July 2012. Patients initiated on TB treatment aged 15 years and above with a known treatment outcome were included in the study. Results The study included 10 251TB patients registered during the study period who had a final treatment outcome and 55.35% (5 674) were males. The mean age was 36.0 years and 72.20% (7398) were new cases. Most patients had pulmonary TB (83.21%). Almost half of the patients (49.62%) were co-infected with HIV. Of the 10 251 cases, 47.02% (4 820) completed treatment, 37.43% (3 837) were cured, 8.67% (889) defaulted, 5.18% (531) died and 1.70% (147) failed treatment. There was a significant association between treatment outcome and sex, disease classification, treatment regimen, HIV status and patient category. Conclusion A high proportion of incident TB cases had previously been treated for TB. Overall treatment outcomes were poor. Unfavourable treatment outcomes were more common in men, those with extra pulmonary TB, retreatment patients and those co-infected with HIV.